Different properties between patients with combined pulmonary fibrosis and emphysema and patients with idiopathic pulmonary fibrosis (Annals of Medical Research, 2022)
Aim: Combined pulmonary fibrosis and emphysema (CPFE) and idiopathic pulmonary fibrosis (IPF) have been discussed intensively in recent years as two different entities. We aimed to compare the clinical, functional and respiratory parameters, clinical course and mortality rates of patients with CPFE with IPF.Materials and Methods: 36 patients with a diagnosis of CPFE and 40 IPF who applied between September 2013 and February 2019 were retrospectively included in the study. Demographic data, comorbidities, pulmonary function parameters, life surveys, systolic pulmonary artery pressures(sPAP) detected.Results: In the CPFE patient group, While the ratio of male patients (p=0.02), smoking (p
Keywords: Combined pulmonary fibrosis and emphysema; Idiopathic pulmonary fibrosis; Mortality; Pulmonary function tests; Pulmonary hypertension